Charge collection studies in irradiated HV-CMOS particle detectors - Affolder, A; Andelković, M; Arndt, K; Bates, R; Blue, A; Bortoletto, D; Buttar, C; Caragiulo, P; Cindro, V; Das, D; Dopke, J; Dragone, A; et al. (IOP Publishing, 2016)
Charge collection properties of particle detectors made in HV-CMOS technology were investigated before and after irradiation with reactor neutrons. Two different sensor types were designed and processed in 180 and 350 nm technology by AMS. Edge-TCT and charge collection measurements with electrons from 90Sr source were employed. Diffusion of generated carriers from undepleted substrate contributes significantly to the charge collection before irradiation, while after irradiation the drift contribution prevails as shown by charge measurements at different shaping times. The depleted region at a given bias voltage was found to grow with irradiation in the fluence range of interest for strip detectors at the HL-LHC. This leads to large gains in the measured charge with respect to the one before irradiation. The increase of the depleted region was attributed to removal of effective acceptors. The evolution of depleted region with fluence was investigated and modeled. Initial studies show a small effect of short term annealing on charge collection.